Laporan Pembangunan Projek Pembangunan Sistem Pengurusan Idea - Shaharudin Ismail; Noorhafizah Abdullah (Universiti Sains Islam Malaysia, 2024)
It is very important to gain knowledge. In order to gain knowledge, we must start from the beginning, which started from gathering and capturing ideas. Each of us is able to come up with creative and innovative ideas. Those ideas might be useful in producing new innovative products. However, the problem regarding gaining knowlegde is how to record and manage these ideas. Nowadays, knowledge management (KM) is expanding, and there is a need to manage knowledge effectively. In order to manage knowledge effectively, organisations have to develop the KM system. The Idea Management System is one of the early steps taken by the Center of Knowledge Management and Information Technology (PPITM) at Islamic Science University of Malaysia (USIM) to manage knowledge. Hopefully, by using this system, users could still contribute their innovative and creative ideas without facing traditional constrain such as lack of time and no suitable platform. USIM's staff and students can contribute their innovative and creative ideas into this system, which will capture and store those ideas. Their ideas could be channeled to the right persons or groups who then could produce new innovative products.